Keynote Address: The Aesthetic Qualities of Aboriginal Writing - Armstrong, Jeannette (Studies in Canadian Literature)

(untitled) (The University of New Brunswick, 2006)
For the Aboriginal storyteller, the politics of story and the act of telling involves mediating the relationship between languages and the world views they produce and represent. As Armstrong explains, for Aboriginal storytellers, this process requires an awareness of how non-linear First Language literature has been transformed by the linear imperatives of the English language and White Western scholarship. Dualities present in original language texts are often compromised when translated into English, and must be recovered, if not re-imagined, by the Aboriginal storyteller whose ability to create “the thread which becomes history” can subvert English literary aesthetics and ensure cultural autonomy. First Language writers and scholars must keep in mind the specific challenges faced by Aboriginal storytellers from various historical periods in order to fully understand the real power and aesthetic of those works. N. Scott Momaday’s The Man Made of Words addresses many of these issues, and explains how we might re-imagine and re-story the things that are of us.